2011
DOI: 10.1166/jnn.2011.5099
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Schemes of Copper(I) <I>N</I>,<I>N</I>′-Diisopropylacetamidinate During Chemical Vapor Deposition of Copper

Abstract: Copper(I) N,N'-diisopropylacetamidinate [Cu(amd)]2 (amd = CH(CH3)2NC(CH3)NCH(CH3)2), an oxygen and halogen-free compound, was previously tested as precursor for pure copper CVD and ALD films. The present work deals with the investigation of the composition and of the reactivity of the gas phase during the CVD process. The work was performed by mass spectrometry as a function of temperature in two different, though complementary environments: (A) in a miniature, low pressure hot wall CVD reactor, (B) in a cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…36 This corroborated decomposition work that was under taken at UC-Riverside. 37 These works highlight the fact that the copper amidinate compounds undergo very slow decomposition at 140…”
Section: Amidinatessupporting
confidence: 69%
“…36 This corroborated decomposition work that was under taken at UC-Riverside. 37 These works highlight the fact that the copper amidinate compounds undergo very slow decomposition at 140…”
Section: Amidinatessupporting
confidence: 69%
“…This same group found that this precursor would decompose at 140°C without hydrogen. [105] This corroborated decomposition work that was under taken at UC-Riverside. [106] These works highlight the fact that the copper amidinate compounds undergo very slow decomposition at 140°C that accelerates when temperatures reach >200°C.…”
Section: Amidinatessupporting
confidence: 69%
“…Copper(I)-N,N'-di-isopropylacetamidinate has been shown to undergo CVD deposition as low as 140°C, [122,125] and produces free amidine, acetonitrile, propene and iminopropane when allowed to thermally decompose in the absence of a reducing agent. [126] These findings have been corroborated in the surface study work of copper(I) acetamidinates on nickel where, above 130°C, the selflimiting nature of the monolayer is compromised and continuous uptake of the copper precursor is observed. Similar ligand fragments were identifed in the surface work as in the gas phase work.…”
Section: Introductionmentioning
confidence: 60%
“…This is the topic of the present paper. We report on the influence of ex situ and/or in situ treatments of the surface of polymer composites on the morphological characteristics and on the growth rate of Cu films processed by MOCVD from (hfac)Cu(I)(MHY) (Gigacopper®) where (hfac) is hexafluoroacetylacetonate and (MHY) is 2-methyl-1-hexen-3-yne [4][5][6] and from copper(I) N,N′-diisopropylacetamidinate, ([Cu(amd) 2 ]) [7,8]. We investigate six surface pre-treatments, namely (i) mechanical polishing and (ii) chemical etching aiming at the formation of a controlled surface roughness and thus enhancement of mechanical anchoring of the metal, (iii) degasing of the composite aiming at desorption of contaminants, (iv) UV photooxidation in air aiming at the replacement of non-polar C\C and C\H bonds by polar O\C = O ones, (v) flush of the substrate with H 2 O vapors during the first steps of the deposition aiming at the creation of \OH functional groups and at the formation of a metal oxide interphase between the polymer and the pure metal, and finally (vi) the grafting of a thin polydopamine interlayer.…”
Section: Introductionmentioning
confidence: 99%